Kinetic modeling of butane-2, 3-diol dehydration over Nb2O5.nH2O. (February 2019) - Cheng, Gui-Lin; Wang, Lin-Yan; Jiang, Cheng-Jun
This study employed Nb2 O5 .nH2 O for the dehydration of butane-2, 3-diol, which could be derived from biomass or waste gas using a fermentation process. The experiments were conducted at a temperature ranging from 220 °C to 260 °C and a weight hourly space velocity of 0.01–0.05 min −1 . There are three main products that include methyl ethyl ketone, isobutyraldehyde, and butadiene. The yield of products increased with the reaction temperature. Rate data for the dehydration reaction were well represented by Langmuir–Hinshelwood kinetics with adsorption parameters in the rate equations, which assumed the formation of products was reversible with single-site reaction. The apparent activation energies for the dehydration reaction of methyl ethyl ketone, isobutyraldehyde, and butadiene obtained from the Arrhenius plot data were 19.5, 24.0, and 23.7 kJ mol −1, respectively. The adsorption energies for butane-2, 3-diol, methyl ethyl ketone, isobutyraldehyde, and butadiene were −182.4, −142.1, −136.1, and −105.6 kJ mol −1, respectively.